Correlation of Hip Passive Range of Motion with Lower Limbs Injuries in Iranian Professional Soccer Players: Hip ROM correlates with injuries - Angoorani, Hooman; Karaminia, Elham; Mazaherinezhad, Ali; Hassanmirzaei , Bahar; Moghadam, Navid (Journal of Clinical Physiotherapy Research, 2021)
Introduction: This study aimed to evaluate the association between hip passive range of motion (ROM) and lower limb injuries in Iranian professional soccer players. Material and Methods: This prospective cohort study was conducted on 266 male professional soccer players (mean age: 24.91 years) playing in Iran Soccer Premium League during seasons 2017-2018 and 2018-2019. Hip joint passive ROM at baseline was evaluated in all athletes. Then, athletes were followed for two consecutive playing seasons and lower limb injuries, which caused missing at least one competitive match, was recorded. The association between hip ROM and the incidence of lower limb injuries was analyzed. Results: The most common lower limb injuries were ankle and foot injuries (12.4%), groin pain (11.5%), and muscle strain (10.9%), respectively. Non-injured athletes had a significantly higher left abduction and bilateral internal rotation (IR) ROM than normal ROM. Right side injury was associated with significantly higher contralateral flexion and external rotation (ER) and left side injury was associated with a significantly higher contralateral extension, abduction, and IR. Restricted hip IR was associated with a higher incidence of groin pain (OR=2.06), ACL injury (OR=2.56), and knee injuries (OR=4.18). A significant correlation was observed between decreased hip ER with muscle strain (OR=1.89) and knee injuries (OR=4.25). The higher knee and ACL injuries were also associated with reduced hip abduction (OR=4.76 and 9.01, respectively). There was no association between ankle and foot injuries and hip passive ROM. Conclusions: This study indicated that hip passive ROM could be used to identify soccer players at higher risk of lower limb injuries. Hip rotational ROM and abduction limitation were significantly associated with incidence of several common soccer injuries, including groin pain, muscle strain, and ACL/knee injuries. Hip rotational ROM and abduction limitation can be used as a screening tool in professional male soccer players.